Human Development and Universalism: From Ideas to Policies*. Issue 2 (3rd April 2019) - Jahan, Selim
Abstract: Human development is about the freedom to realize the full potential of every human life, not just for a few, not for the most, but of all lives in every corner of the world—now and in the future. Human development is for everyone and that universalism is at the core of the human development concept and framework. The paper argues that universalism as a principle is one thing, translating it into practice is another. That is where practical universalism comes in, the first steps of which are identifying the groups, which have been left behind in the human development journey and analyzing the barriers to universalism. The paper emphasizes that mapping of those left out is necessary and so is the identification of barriers, but not enough. Some fundamental issues of the human development framework—both in terms of notions as well as measurements—need to be addressed to move towards universal human development. Furthermore, universal human development would also require policy actions at the national level and reforms of global institutions. The paper concludes with the fundamental point that ensuring human development for everyone would require reaching those first who are farthest behind.